Study on Vibration Characteristics of a Shipboard Helicopter Tail Horizontal Shaft System with an End Gear Folding Mechanism - Li Miaomiao; Zhang Zhao; Zhu Rupeng; Wang Xi; Liang Fudong (Jixie chuandong)
An end gear folding mechanism allows for folding of the tail horizontal shaft system, increasing the number of shipboard helicopters that can be docked on aircraft carriers. At the same time, the end gear folding mechanism affects the vibration characteristics of the helicopter tail horizontal shaft system. A dynamic model of a shipboard helicopter end-tooth folding tail horizontal shaft system was established, and the vibration response of each support of the shaft system was solved and analyzed. Firstly, based on the finite element method and the strain energy method, the equivalent simplification of the spline connection part and the end-tooth connection part in the folding mechanism was carried out respectively, the spline connection part was equivalent to the radial stiffness and the corner stiffness, the end-tooth connection part was equivalent to the equivalent ring, the dynamics model of the end-tooth folding mechanism was established, and the accuracy of the modeling method was verified by comparing the modal analysis results with the finite element simulation. On this basis, the folding device dynamics model was coupled to the tail horizontal shaft system, and the folding tail horizontal shaft system dynamics model was established to solve and analyze the vibration characteristics of the shaft system. The results of the study show that in each support, the largest displacement response is at the joint bearing, and the smallest is at the main reduction output end bearing. The vibration response is related to the support position and its stiffness damping characteristics. This study provides theoretical guidance for the study of the shaft system support configuration.